Contemporary western European feminism - Kaplan, Gisela (London, 1992)
""[A]n exciting, theoretically sophisticated and excellently documented contribution to feminist literature . . . . a timely case study of the feminisms that have emerged in response to national, ethnic, class-based, and international pressures throughout Western Europe . . . . politically astute and methodologically impeccable . . . . The scope is clearly stated; the goods promised are all delivered; the author's awesome linguistic skills have allowed for the use of particularly rich source materials not normally available to English speaking readers; and the very impressive bibliography allows what is a coherent whole to serve also as a stepping stone to further explorations . . . . a unique contribution to the comparative understanding of social movements. It will be indispensable for women's studies courses and should be read by all feminist theorists."